Compensatory policies adopted by Belize: country paper - Bennett, Edney F. (ILO PREALC Port of SpainTT, 1991)
Reviews the performance of the Belizean economy during the 1985-89 period. Highlights some of the major developments within the following areas viz. production, investment, public sector finances, international trade and balance of payments and employment. Identifies remedial measures undertaken at the national level to counteract the negative social impact of structural adjustment measures.